P176 Preliminary results of 'at risk' asthma and COPD reviews by specialist teams in primary care. (December 2018) - Ray, E; Kruk, H; Gillett, K; Culliford, D; Lin, X; Price, D; Thomas, DM; Wilkinson, T
Abstract : Background: Respiratory disease is a common cause for primary care consultations, and increasingly, patients with complex and 'high-risk' lung disease are managed in the community. Variation in the quality of community management of 'high-risk' patients may lead to sub-optimal outcomes for some. The ASSIST study (REC: 16/5C/0629) has implemented a complex intervention aimed at identifying and optimising the management of asthma and/or COPD patients in primary care, in 'at risk' patients. Method: Patients with documented asthma and/or COPD were identified through 'Read code' searches of GP practice records. A DOSE score ≥3 defined 'at risk' COPD patients, whilst 'at risk' asthma patients were defined using a search algorithm identifying factors associated with poor control (including previous exacerbations and high bronchodilator requirements). The DOSE and asthma algorithms were run in 12 and 8 GP practices respectively. All eligible patients were invited to attend their GP practice for a specialist respiratory review. Results: A total of 464 patients were invited, 66 responded but only 35 were enrolled onto the study due to exclusions and drop-outs. 54% were male with a mean age of 67.23 (SD: 13.07). 16 (46%) patients had asthma, 15 (43%) had COPD, 4 (11%) had asthma/COPD overlap (ACO). Mean pack year was 40.96 (SD: 30.62), 4 patients (11%) were current-smokers, whilst 7 (20%) were never-smokers. Median FEV1 was 1.43 litres (IQR 0.97–2.17) and FEV1 % predicted was 61% (IQR: 41%–109%). The primary diagnosis was changed in 12 (34%) patients. Changes to inhaled medications were recommended in 18 (51%) cases (including change of device/s, and/or addition of spacers), further tests were requested in 17 (49%) cases and onward referral for specialist review was advised in 19 (54%) cases. Conclusions: It is possible to identify high-risk patients from electronic GP record searches, although only a minority will attend, when invited, for subsequent review. Actions to improve outcomes, including diagnosis and treatment changes and onward referral, resulted for most patients. 12 month follow up data will evaluate patient reported outcomes, health care resource usage and overall cost effectiveness of the intervention.